Voices from the Contemporary Japanese Feminist Movement - Dalton, Emma. author. aut Link
IX, 137 p. 1 illus.
Keywords: This book introduces six key influential feminist activists from Japan’s contemporary feminist movement and examines Japanese women’s experience of and contribution to the international #MeToo movement. Set against a backdrop of pervasive sexual inequality in Japanese society—on a scale that makes Japan an outlier in Asia as well as the rest of the advanced democratic world—this book offers a snapshot of Japan’s contemporary feminist movement and the issues it faces, including, primarily, sexual violence and harassment of women and girls. The six feminist activists interviewed to create this snapshot all work toward eradicating sexual violence against women and girls—they are: Kitahara Minori (instigator of the Flower Demo and public commentator), Yamamoto Jun (activist for sex crime law amendments), Nitō Yumeno (advocate for sexually exploited girls), Tsunoda Yukiko (feminist lawyer), Mitsui Mariko (former politician and current activist), and Yang-Ching-Ja (comfort women activist). Emma Dalton is lecturer in Japanese Studies in the Department of Languages and Cultures at La Trobe University, Melbourne, Australia. She is the author of Sexual Harassment in Japanese Politics (2021) and Women and Politics in Contemporary Japan (2015). Caroline Norma lectures in the Master of Translating and Interpreting degree at RMIT University in Australia. She is the author of Comfort Women and Post-Occupation Corporate Japan (2018) and The Japanese Comfort Women and Sexual Slavery During the China and Pacific Wars (2015).